Review of the impacts of leaking CO2 gas and brine on groundwater quality - Qafoku, Nikolla P.; Lawter, Amanda R.; Bacon, Diana H.; Zheng, Liange; Kyle, Jennifer; Brown, Christopher F. (Earth-science reviews, 2017)
This paper provides an overview of the existing data and knowledge presented in recent literature about the potential leaking of CO2 from the deep subsurface storage reservoirs and the effects on groundwater quality. The objectives are to: 1) present data and discuss potential risks associated with the groundwater quality degradation due to CO2 gas and brine exposure; 2) identify the set of geochemical data required to develop models to assess and predict aquifer responses to CO2 and brine leakage; and 3) present a summary of the findings and reveal future trends in this important and expanding research area. The discussion is focused around aquifer responses to CO2 gas and brine exposure and the degree of impact; major hydrogeological and geochemical processes and site-specific properties known to control aquifer quality under CO2 exposure conditions; contributions from the deep reservoirs (plume characteristics and composition); and the possibility of establishment of a new network of reactions and processes affecting or controlling the overall mobility of major, minor, and trace elements and the fate of the elements released from sediments or transported with brine. This paper also includes a discussion on the development of conceptual and reduced order models (ROMs) to describe and predict aquifer responses and whether or not the release of metals following exposure to CO2 is harmful, which are an essential tool for CO2 sequestration related risk assessment. Future research needs in this area are also included at the end of the paper.